Operations research proceedings 2017 : selected papers of the annual International Conference of the German Operations Research Society (GOR), Freie Universiät Berlin, Germany, September 6-8, 2017 /: selected papers of the annual International Conference of the German Operations Research Society (GOR), Freie Universiät Berlin, Germany, September 6-8, 2017. ([2018]) - Unknown
No abstract available